2020
DOI: 10.3390/su12124857
|View full text |Cite
|
Sign up to set email alerts
|

Social Responsibility, Communication and Financial Data of Hospitals: A Structural Modelling Approach in a Sustainability Scope

Abstract: Health is one of the fundamental pillars of public management and should be one of the main objectives of any society that pursues true progress and well-being for its citizens. In recent years, the public health system has been seeking collaborative synergies with the private health system to achieve efficient functioning at the levels of care demand, waiting lists and financial pressure. For this reason, private entities in the hospital field must be analysed through the application of information systems co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 111 publications
0
4
0
Order By: Relevance
“…The cause-effect relations between latent constructs in social science and management research are considered appropriately examined by using structural equation modeling (SEM; Hair et al, 2011 ). PLS-SEM estimation is more resistant to potential violations of normality than covariance-based SEM ( Creixans-Tenas et al, 2020 ). Bootstrapping of 3,000 resamples was used to generate SEs, t -statistics, and confidence intervals to assess the statistical significance of the path coefficients.…”
Section: Methodsmentioning
confidence: 99%
“…The cause-effect relations between latent constructs in social science and management research are considered appropriately examined by using structural equation modeling (SEM; Hair et al, 2011 ). PLS-SEM estimation is more resistant to potential violations of normality than covariance-based SEM ( Creixans-Tenas et al, 2020 ). Bootstrapping of 3,000 resamples was used to generate SEs, t -statistics, and confidence intervals to assess the statistical significance of the path coefficients.…”
Section: Methodsmentioning
confidence: 99%
“…But in times of ambiguities, transparent communication will guide unsure GPs on which RHS to trust as a partner or continue its relationship with [ 31 ]. Moreover, adopting transparency will increase the reputation and positive image of the stakeholders and create an opportunity to acquire consensus and appreciation from all the stakeholders in the partnership [ 32 , 33 ]. Our study findings showed no issues where the GPs and the RHS had to negotiate to reach a consensus.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, structural equation modeling can establish a complex multivariate relationship based on the covariance matrix of variables and simulate the internal logic between multiple factors, which can effectively deal with such problems [13][14][15]. Structural equation modeling can be used to study plan demand structure to explain quantitative relationships among multiple variables, simplify complex models, and reasonably deal with ambiguities in quantifying demand factors to provide an impact basis for scale expansion [16][17][18]. Therefore, this paper uses structural equation modeling to deal with the relationship between individual variables and explore the impact of higher education scale expansion on human capital accumulation and economic development through the relationship between latent variables and latent variables.…”
Section: Structural Equation Modelmentioning
confidence: 99%